New graduate employment in general practice: Perceptions of final-year nursing students. (July 2021) - Calma, Kaara Ray B.; Williams, Anna; McInnes, Susan; Halcomb, Elizabeth
Abstract: Aim/objective: This paper sought to investigate the perceptions of final-year nursing students regarding general practice nursing as a new graduate career path. Background: General practice nurses have become increasingly important in providing community-based care, in response to the growing burden of chronic conditions and the ageing population. To sustain this workforce, there is a need to optimise strategies to promote a consistent supply of new graduate nurses. Design: This qualitative descriptive study was undertaken within a sequential explanatory mixed methods project. Methods: Data were collected through semi-structured telephone interviews with sixteen final-year nursing students from five Australian universities. Interviews were analysed using thematic analysis. Results: Four main themes were identified, namely; a) general practice is not a priority career path, b) opportunities for skills development and consolidation, c) perceptions of employment conditions, and d) transition support is limited. Conclusion: To meet current workforce needs in areas with increasing demand, nurse educators need to support undergraduate nursing students to explore a wide range of career pathways following graduation. Informed career choices and well-structured educational preparation during undergraduate education may be an effective strategy in building a sustainable future workforce in settings such as general practice. Tweetable abstract: General practice nurses play a key role in addressing the growing needs of the community. This study revealed that final-year nursing students don't always consider a career path in general practice as they are not well exposed to this setting in their undergraduate preparation. Highlights: Supporting nursing students to consider diverse career paths should be a priority. General practice was not a priority career path immediately following graduation. Perceptions varied about opportunities to develop clinical skills in this setting. General practice was perceived as 'light' work, but enabled better work-life balance. There is a need to enhance transition support for new graduates in this setting.